ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI UNDERPRICING SAHAM PADA INTIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA (BEI) TAHUN 2022 - Nurshabani, Tasya; Ferranti, Putri Andari (Journal of Fundamental Management (JFM), 2024)
This study aims to determine and analyze Underwriter Reputation, Auditor Reputation, Company Size, Proceeds, and Financial Leverage on Stock Underpricing. The population in this study were companies that made on  Initial Public Offering (IPO) on the Indonesia Stock Exchange in 2022. Sampling technique with purposive sampling method. From this method obtained 37 companies were obtained that met the criteria during the observation period. The data analysis method uses quantitative analysis.  The research design used was casual research using multiple linear regression analysis using the E-Views 12 application to determine the level of significance between the dependent variable and the independent variable. The results can show that Auditor Reputation and Company Size have a positive and significant influence on Underpricing, Proceeds have a negative and significant influence on Underpricing, Underwriter Reputation and Financial Leverage do not affect Underpricing that conducts an Intial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) in 2022.